How Knowledge Management, Technology Information, Employee Performance and Employee Satisfaction Work Together - Refa, Nurefa Maulana; Nayati Utami , Hamidah; Afrianty, Tri Wulida (Profit: Jurnal Adminsitrasi Bisnis, 2024)
The study's primary objectives are to determine how knowledge management and information technology affect employee performance, with employee satisfaction as an intervening variable. Information technology and knowledge management are crucial components of employee performance support in Easterntext. Scientists likewise estimated worker fulfillment as a mediating variable on employee performance. In order to ascertain the effects, knowledge management and information technology are used as variables to measure employee performance and employee satisfaction within the company. This study utilized an informative exploration approach with 92 respondents of the probability sampling method. SmartPLS 3 and partial least square structural equation modeling (PLS-SEM) were utilized for data analysis. The outcomes showed that knowledge management and technology information impacted employee performance through employee satisfaction at Easterentex. In this way, it is realized that the variable knowledge management, technology information, and employee satisfaction support and contribute to worker performance.